Pseudomonas alloputida and Pseudomonas taiwanensis in a process of degradation of polymer materials - Mazuryk, Alicja; Lisewska, Daria; Fiedurek, Kacper; Janczak, Katarzyna (European Journal of Sustainable Development, 2024)
The literature indicates that the source of microorganisms with the potential of polymer biodegradation may be in particular anthropogenically degraded areas such as landfills, contaminated areas of former factories and processing plants. These environments often contain polymer waste, especially in the form of microplastics. Biodegradation is a significant microbiological process in which bacteria or fungi with hydrolytic activity are essential. Polylactide (PLA) is one of the most commonly used biodegradable polymer materials. Its biodegradation in mesophilic conditions is difficult due to too low temperature. In order to improve and accelerate this process, microorganisms that can be effective in mesophilic biodegradation of PLA were selected. Isolated environmental bacteria, Pseudomonas alloputida and Pseudomonas taiwanensis, were identified as high hydrolytic towards complex organic compounds and polymer materials. They accelerate the degradation of PLA, as demonstrated by the results of infrared Fourier analysis (FTIR-ATR), SEM-EDX microscopic analysis and physico-mechanical values. Obtained results indicate the application potential of the tested bacteria to significantly decrease soil and compost contamination. Keywords: biodegradation, polylactide, hydrolytic activity, environmental bacteria